2013
DOI: 10.7448/ias.16.4.18749
|View full text |Cite
|
Sign up to set email alerts
|

“They are human beings, they are Swazi”: intersecting stigmas and the positive health, dignity and prevention needs of HIV‐positive men who have sex with men in Swaziland

Abstract: IntroductionDespite the knowledge that men who have sex with men (MSM) are more likely to be infected with HIV across settings, there has been little investigation of the experiences of MSM who are living with HIV in sub-Saharan Africa. Using the framework of positive health, dignity and prevention, we explored the experiences and HIV prevention, care and treatment needs of MSM who are living with HIV in Swaziland.MethodsWe conducted 40 in-depth interviews with 20 HIV-positive MSM, 16 interviews with key infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
120
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 14 publications
5
120
0
Order By: Relevance
“…Studies conducted in Tanzania [7], Malawi [14,34], Swaziland [9,10] and Uganda [35] point to stigma and homophobia as significant factors affecting HIV risk among the MSM in these countries. Fewer recent works from West and Central Africa focused on the roles of homophobia and stigma in exacerbating HIV risk for MSM, but these factors are almost ubiquitously discussed as the background context for MSM research in this region [cf.…”
Section: Broad Level Risk Factors: Public Policy and Socio-cultural Cmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies conducted in Tanzania [7], Malawi [14,34], Swaziland [9,10] and Uganda [35] point to stigma and homophobia as significant factors affecting HIV risk among the MSM in these countries. Fewer recent works from West and Central Africa focused on the roles of homophobia and stigma in exacerbating HIV risk for MSM, but these factors are almost ubiquitously discussed as the background context for MSM research in this region [cf.…”
Section: Broad Level Risk Factors: Public Policy and Socio-cultural Cmentioning
confidence: 96%
“…Additional barriers to implementation include high levels of stigma and homoprejudice across the region [5•, 6-8], a lack of knowledge of the specific needs of MSM in terms of HIV prevention among health care workers and public health officials [9][10][11] and a lack of resources specifically targeted at MSM populations [12]. In spite of these challenges, however, there is an increasing focus on MSM in HIV-related research in SSA, which may, in turn, facilitate the development of appropriate prevention, treatment and care strategies for this population.…”
Section: Introductionmentioning
confidence: 99%
“…The 2009–2014 Swaziland National Multi-Sectoral Strategic Framework for HIV and AIDS [39] noted that “Quality and reliable data are largely lacking for most of the key populations,” and attributed this gap to “lack of prioritization of such populations in prevention programmes.” R2P collaborated with the Swaziland Ministry of Health and other NGOs to conduct a quantitative survey using respondent-driven sampling to estimate population-level prevalence of HIV and risk factors among MSM and FSW in Swaziland [4046]. The project also included complementary qualitative research including in-depth interviews and focus group discussions among MSM and FSW living with HIV to understand their experiences and unique needs in prevention, care and treatment services [47, 48]. In this study, HIV prevalence was estimated at 60.5% among FSW and 12.6% for MSM [40, 49].…”
Section: Prioritizing the Needs Of Underserved Groups: Using Data To mentioning
confidence: 99%
“…Where homosexuality is criminalised, studies have shown that MSM avoid accessing HIV prevention services due to fear of being persecuted, extorted or blackmailed 6 7 . W4 Dramatic reductions in access to HIV services have also been observed immediately after laws criminalising homosexuality were put into place 8 .…”
Section: Introductionmentioning
confidence: 99%